Inside Cover Image. (6th March 2020) - Gottwald, Lukas M.; Peper, Eva S.; Zhang, Qinwei; Coolen, Bram F.; Strijkers, Gustav J.; Nederveen, Aart J.; van Ooij, Pim
Abstract : The cover image is based on the Research Article Pseudo‐spiral sampling and compressed sensing reconstruction provides flexibility of temporal resolution in accelerated aortic 4D flow MRI: A comparison with k‐t principal component analysis by Lukas M. Gottwald et al., https://doi.org/10.1002/nbm.4255 .